2010
DOI: 10.1017/s1743921310016078
|View full text |Cite
|
Sign up to set email alerts
|

Investigating accretion disk – radio jet coupling across the stellar mass scale

Abstract: Abstract. Relationships between the X-ray and radio behavior of black hole X-ray binaries during outbursts have established a fundamental coupling between the accretion disks and radio jets in these systems. I begin by reviewing the prevailing paradigm for this disk-jet coupling, also highlighting what we know about similarities and differences with neutron star and white dwarf binaries. Until recently, this paradigm had not been directly tested with dedicated high-angular resolution radio imaging over entire … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 23 publications
5
23
0
Order By: Relevance
“…In the novalikes, the radio emission is non-thermal, and is consistent with synchrotron or coherent emission (Coppejans et al 2015). In the DN SS Cyg, the radio emission in outburst is explained as synchrotron emission from a transient jet (Körding et al 2008;Miller-Jones et al 2011;Russell et al 2016). We now discuss what type of radio emission is seen in our sample of DN.…”
Section: Radio Emission Mechanism In Dn Outburstsmentioning
confidence: 62%
See 4 more Smart Citations
“…In the novalikes, the radio emission is non-thermal, and is consistent with synchrotron or coherent emission (Coppejans et al 2015). In the DN SS Cyg, the radio emission in outburst is explained as synchrotron emission from a transient jet (Körding et al 2008;Miller-Jones et al 2011;Russell et al 2016). We now discuss what type of radio emission is seen in our sample of DN.…”
Section: Radio Emission Mechanism In Dn Outburstsmentioning
confidence: 62%
“…They predicted that DN should show a synchrotron radio flare from a transient jet on the rise to outburst, and they detected this in the DN SS Cyg. Miller-Jones et al (2011) subsequently confirmed this behaviour in a separate outburst of SS Cyg, and Russell et al (2016) proved that the radio outbursts of SS Cyg undergo similar evolution from outburst to outburst. Based on the timing, variability, spectral indices and brightness temperatures of the radio emission, and multi-wavelength data, Körding et al (2008), Miller-Jones et al (2011) and Russell et al (2016) argue that the radio emission in SS Cyg is produced by a transient jet.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations